2010
DOI: 10.1143/ptps.185.197
|View full text |Cite
|
Sign up to set email alerts
|

+,K+) Reaction Spectroscopy of Heavy Hypernuclei

Abstract: For the last few decades the (π + , K + ) reaction has played an important role in heavy hypernuclear spectroscopy where the Λ spin-orbit splitting should be one of the most interesting subjects. In this article, first, various stages of calculational frameworks for hypernuclear production cross sections are discussed. Then, focusing on the 89 Y(π + , K + ) 89 Λ Y experimental data, new DWIA analysis has been carried out by taking full account of the core nuclear excitation effects. As a result we found that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 18 publications
9
60
0
Order By: Relevance
“…It is found that the present calculation with Gogny D1S reproduces the level ordering except for the 1/2 − state in 9 Be and 9 B. However, the excitation energies are slightly lower than the experimental data in 8 Be, 9 Be and 9 B. Since they have the well-developed 2α cluster structure, it is considered that the difference of the excitation energies shows the overestimation of the momentum of inertia of the the 2α clustering.…”
Section: Numerical Results and Discussionmentioning
confidence: 42%
See 4 more Smart Citations
“…It is found that the present calculation with Gogny D1S reproduces the level ordering except for the 1/2 − state in 9 Be and 9 B. However, the excitation energies are slightly lower than the experimental data in 8 Be, 9 Be and 9 B. Since they have the well-developed 2α cluster structure, it is considered that the difference of the excitation energies shows the overestimation of the momentum of inertia of the the 2α clustering.…”
Section: Numerical Results and Discussionmentioning
confidence: 42%
“…We perform the antisymmetrized molecular dynamics (AMD) calculation for 6 Li, 8 Li, 8 Be, 9 Be, 9 B, 10 B, 11 C, 12 C, 14 N, and 15 O using the original parameter set of Gogny D1S given in Refs. [29,30].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations